As tramas do racismo à brasileira: o ensino da História e Cultura Afro-brasileira nas instituições escolares de Itapagipe/MG (2003-2006) - Barbosa, Maria Rita de Jesus (2017)
The research presented addresses racism from the analysis of application, or not, of Law No. 10.639 / 03, and as a research field two public elementary schools in the city of Itapagipe / MG. Law 10.639 / 2003, as amended by law No. 11,645 / 2008, but without losing its essential nature, is the mandatory teaching of African history and African. During the research it was read and consulted several bibliographical sources aimed to understand and analyze the historically discourse built around the marginalization of black and Afro-descendant population, as well as the continuity of racism, observed in everyday relationships within schools. The qualitative methodology was the basis of this research, with the support of quantitative and qualitative data received from empirical observation in schools, not only as a researcher, but as an effective teacher of these institutions, the application of questionnaires to teachers and students, the discursive analysis responses obtained in interviews with teachers, principals, secretaries of schools, residents of Itapagipe, social worker and the municipal secretary of education among other documentary sources. The discussions were informed by authors such as Kabengele Munanga, Dagoberto da Fonseca, Lilia Schwarcz. Through dialogue with the various aforementioned sources it was possible to demonstrate the maintenance of racism in schools, in the words of the secretaries to describe racism as inherent to blacks themselves and ignorance and disbelief from educators regarding Law 10.639 / 03, as order the construction and strengthening the African-Brazilian identity, from the recognition of the legacy of history and Afro-Brazilian and African culture.